2022
DOI: 10.1177/10600280221115889
|View full text |Cite
|
Sign up to set email alerts
|

Difelikefalin: A New κ-Opioid Receptor Agonist for the Treatment of Hemodialysis-Dependent Chronic Kidney Disease–Associated Pruritus

Abstract: Objective: To review data for difelikefalin (Korsuva) intravenous solution for management of moderate-to-severe pruritus in hemodialysis (HD) patients. Data Sources: Literature search of PubMed (January 1946-May 2022) and SCOPUS (January 1946-May 2022) was performed using the terms: Korsuva, CR845, and difelikefalin. Additional information sources include ClinicalTrials.gov, prescribing information, meeting posters, and references of identified articles. Study Selection and Data Extraction: Clinical trials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Forth, minor improvement of VAS manifests limited role of CHM in relieving uremic pruritus in dialysis patients. Last, about thirty percent of UP patients benefits from placebo effect while comparing to Difelikefalin ( Fugal and Serpa, 2022 ). However, lack of placebo comparison in control groups from included RCTs in our study might affect the result of effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forth, minor improvement of VAS manifests limited role of CHM in relieving uremic pruritus in dialysis patients. Last, about thirty percent of UP patients benefits from placebo effect while comparing to Difelikefalin ( Fugal and Serpa, 2022 ). However, lack of placebo comparison in control groups from included RCTs in our study might affect the result of effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of UP is complicated; it is associated with various inflammatory mediators, neurotransmitters, and opioids. Treatments for UP, including difelikefalin, gabapentin, antihistamines, and phototherapy, have anti-pruritic effects, although adverse drug reactions (ADR), such as diarrhea, vomiting, somnolence, and dizziness, have been reported for some ( Hercz et al, 2020 ; Trachtenberg et al, 2020 ; Fugal and Serpa, 2022 ; Ko et al, 2022 ). The use of UVB radiation in phototherapy is associated with an increased risk of malignancy ( Mettang and Kremer, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies proved that, by reducing pruritus intensity, difelikefalin improves the quality of life for patients with CKD-aP. However, the lack of data about its long-term effectiveness is a limitation that further research needs to overcome [ 43 ]. The search for alternative CKD-aP treatment is still ongoing.…”
Section: Discussionmentioning
confidence: 99%
“… 66 , 67 Recently, the US Food and Drug Administration approved difelikefalin, a peripherally restricted and selective KOR agonist for moderate-to-severe CKD-aP. 68 Majority of trials show significant improvement of the CKD-aP conditions; however, no studies reported analyses of kidney function during the treatment. 69 , 70 Phase 3 clinical trials are currently underway for the safety and efficiency of difelikefalin in patients with CKD (Trial registration number NCT05342623 ).…”
Section: Dialysis and Opioid Usementioning
confidence: 99%